The Current Situation and Improvement of Aesthetic Education for Chinese and Foreign College Students in Polytechnic Colleges and Universities Path Exploration — Taking University G as an Example - Fanqi Meng; Shiyu Huang (Journal of Advanced Research in Education, 2025)
Aesthetic education is an education in aesthetics, a form of humanistic education that holds profound significance in cultivating character and shaping personality. One of the keys to carry out the fundamental task is to do a good job in aesthetic education in colleges and universities, which is an important part of improving the educational system in colleges and universities. At present, there are still some problems in science and engineering universities, such as the lack of aesthetic education and the monotonous form of education. Based on the reality of science and engineering aesthetic education, this paper tries to improve the level of aesthetic education by perfecting the curriculum system, optimizing campus culture and establishing a practice platform.